An efficient IoT based biomedical health monitoring and diagnosing system using myRIO - Rathy G. A.; Sivasankar P.; Tamara Z. Fadhil (Universitas Ahmad Dahlan, 2020)
With the growing and aging population, patient auto monitoring systems are becoming more popular. Smart sensors linked with the internet of things (IoT) make patients' auto monitoring system possible. Nowadays myRIO with LabVIEW is more popular for easy data acquisition, instrument control, and automation. This paper proposed myRIO and IoT based health monitoring and diagnosing system (HMDS) to acquire heartbeat rate, pulse, blood pressure (BP), temperature and activities of the patient using various smart sensors with more accuracy. The acquired raw data from the various sensors had been sent to the myRIO using ESP 8266 Wi-Fi module. The received raw data by the myRIO would be processed to the equivalent medical parameters using LabVIEW and the same might be transferred to the remote monitoring system (RMS) using cloud via a gateway. The abnormalities in the obtained data would be monitored and the diagnosis was made. The experimental setup was developed using various wearable sensors, ESP 8266, myRIO with LabVIEW and cloud with the gateway.